Consequences of the three disciplines on the overall result in olympic-distance triathlon - Fröhlich, M.; Klein, M.; Pieter, A.; Emrich, E.; Gießing, J. (International Journal of Sports Science and Engineering, 2008)
Olympic-distance triathlon (OD) is a multidisciplinary sport that comprises three different disciplines which are conducted in succession. Overall triathlon time consists of the three disciplines and the two transition times between the three disciplines. In order to achieve the fastest overall time possible, the times needed for each discipline have to be minimized. The aim of the study was to determine the effects of the three disciplines on the overall result in the OD. Methods: Overall times and rankings as well as rankings and times for each of the three disciplines (swimming, cycling, and running) of all elite athletes (participations of the world championship) who competed in the men`s Olympic-distance triathlon world championships between 2004 and 2007 were analyzed. The sample consisted of 318 athletes, ten of which competed in all of the world championships from 2004 to 2007. Results: The highest correlations (pearson coefficient) between the times of the individual disciplines and the overall time can be found for the run. The correlations were even higher for the 20 best-placed athletes. An athlete`s placing after the swim or the cycle has little prognostic relevance for his final placing. Statistical clearing of variance shows the greatest effect for the run. Conclusions: The swim and the cycle act as so-called feeders for the run and have to lay the foundations for the run, which decides over winning or losing more than the other two disciplines. Judging from an efficiency-oriented perspective, triathletes should emphasize training the run rather than emphasising the swim or the cycle.